Psychological Maladaptation and Resilience: The Experience of Ukrainian Youth During the War - Sodolevska, Валерія (Psychosomatic Medicine and General Practice, 2025)
Introduction. Due to the full-scale invasion of russia in Ukraine, the psychological well-being of Ukrainian youth has become an acute problem. Stressful events and traumatic experiences during the war lead to an increase in cases of depression, anxiety disorders, and stress reactions. Youth is an especially vulnerable group, as they are at a stage of forming psycho-emotional stability, which complicates coping with stressful situations. Resilience, as the ability to adapt to stress and recover from difficulties, can act as a buffer against negative consequences. The aim of the study was to determine the features of maladaptation and resilience factors in youth during the Russian-Ukrainian war. Materials and methods. The study was conducted at the Railway Clinical Hospital No.1 and the Department of Medical Psychology of Bogomolets National Medical University. A total of 146 young people aged 18 to 35 who had experienced traumatic events during the war were examined. Psychodiagnostic questionnaires were used: LEC-5, IES-R, PHQ-9, GAD-7, CD-RISC-10, and the CQLS quality of life scale. Statistical data processing included the Student's t-test, Mann-Whitney test, Pearson and Spearman correlation analysis, and multifactor linear regression analysis. Results. The analysis showed that a significant part of the youth had high levels of anxiety and moderately expressed symptoms of depression. Resilience was inversely proportional to the severity of depression and anxiety, as well as to the number of traumatic events. Older age and marital status were associated with a lower level of resilience, probably due to the accumulation of traumatic experiences and responsibility for the family. Resilience also positively correlated with quality of life, emphasizing its role as a protective factor. Conclusions. The results of the study indicate that Ukrainian youth in war conditions face pronounced manifestations of maladaptation, particularly high levels of anxiety and depression. At the same time, high resilience contributes to better quality of life and reduced emotional distress. Considering the importance of psychological resilience in wartime, it is advisable to develop psychosocial interventions aimed at strengthening youth resilience.